Dimensionamento de unidade de desinfecção por radiação ultravioleta de efluente secundário - Pontes Júnior, Severino Mosinho de (2018)
Effluent generation is an own problem to many processes, which can vary from daily anthropic activities in our homes to the large raw material processing industries, especially due to their polluting potential of the water bodies. Sanitary sewage, moreover, are capable of contaminating springs and enabling the dissemination of waterborne diseases that have a high impact on public health. Therefore, this work proposes the design of a sanitary effluent disinfection unit through UVC germicidal lamps aiming at the inactivation of total and fecal coliform types microorganisms, as well as to solve the problems faced by the use of chlorination as an alternative treatment for effluents secondary sanitary sewers. As a result, it was determined that it is necessary to use two 90 cm lamps and a time of 15 s, considering a maximum flow of 2 m³/h, to reach the adequacy of this wastewater to the emission standards stipulated by the legislation.